2010
DOI: 10.1002/qua.22849
|View full text |Cite
|
Sign up to set email alerts
|

Fast generation of broken‐symmetry states in a large system including multiple iron–sulfur assemblies: Investigation of QM/MM energies, clusters charges, and spin populations

Abstract: A density functional theory study is presented regarding the energetics and the Mulliken population analyses of a quantum mechanical/molecular mechanical (QM/MM) system including multiple iron-sulfur clusters in the QM region. The [FeFe]-hydrogenase from Desulfovibrio desulfuricans was studied, and both the active site (an Fe 6 S 6 assembly generally referred to as the H-cluster) and an ancillary Fe 4 S 4 site were treated at the BP86-RI/TZVP level. The antiferromagnetic coupling that characterizes both sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 42 publications
2
52
1
Order By: Relevance
“…35 The use of the SVP basis has been previously validated. 27 B3LYP gives unpaired spins distributions that are in better agreement with EPR and Mössbauer experimental data when compared with results obtained using pure functionals. 36 However, calculations were carried out also at the BP86/SVP level, and the conclusions one can draw from the latter results are compatible with the picture coming from B3LYP/SVP optimizations (see Supporting Information).…”
supporting
confidence: 77%
“…35 The use of the SVP basis has been previously validated. 27 B3LYP gives unpaired spins distributions that are in better agreement with EPR and Mössbauer experimental data when compared with results obtained using pure functionals. 36 However, calculations were carried out also at the BP86/SVP level, and the conclusions one can draw from the latter results are compatible with the picture coming from B3LYP/SVP optimizations (see Supporting Information).…”
supporting
confidence: 77%
“…In order to obtain such a BS coupling scheme in the various models, we used an approach that we developed recently. [17] QM/MM modeling: In the QM/MM calculations, the protein was divided into three subsystems. System 1 was treated at QM level, and was allowed to relax.…”
Section: Methodsmentioning
confidence: 99%
“…However, in a previous study on [FeFe]-hydrogenases we have shown that the overall Mulliken charges of the Fe 4 S 4 clusters are essentially unaffected by the particular BS wavefunction chosen. [33] All the results reported in the Result and Discussion section are based on the BS coupling scheme shown in Figure 6. The spin excess pattern in the [4 Fe4 S] H subcluster and in the F-and F'-clusters were directly obtained from standard SCF calculations, as described previously.…”
Section: Wwwchemphyschemorgmentioning
confidence: 98%
“…The use of the SVP basis has been validated previously. [33] In the QM calculations, all atoms in system 2 were represented by partial point charges. These charges were included in the Hamiltonian of the QM calculations, and thus the quantum chemical system was polarized by the atoms of system 2 in a self-consistent way.…”
Section: Computational Detailsmentioning
confidence: 99%